Art for Art's Sake: The Rejection of Ethical Value? - Klaeger, Florian (Handbook of Literary Criticism and Ethics, 2026)
The chapter discusses the idea and ideology of “art for art’s sake” in historical context. It argues that the late nineteenth-century aestheticist version of this concept must be seen as a particular configuration with roots stretching back to antiquity. It presents a number of systematic clusters proposed by historians of aesthetics for approaching art for art’s sake and explores key elements of the debates in which the idea was fielded. These include the artwork’s autonomy, its reference to external reality, its value and utility (including the obligation to moral didacticism), and the shifting roles of critics and of audiences/readers.